2020
DOI: 10.1177/0193945920902146
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Components Targeting Self-Management in Individuals with Multiple Chronic Conditions: An Integrative Review

Abstract: Multiple chronic conditions (MCC) are becoming increasingly common and self-management (SM) interventions to address MCC are emerging. Prior reviews have broadly examined SM interventions in MCC; however, interventional components were not thoroughly described. Components of SM interventions that have been delivered to individuals with MCC were identified. A review of CINAHL, Cochrane, PubMed, PsycINFO, Scopus, and Embase was completed. This search yielded 13,994 potential studies; 31 studies among those 13,99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…No date criteria were used in our search strategy, but all six reviews were published after 2015. Methods varied as follows: one review identified itself as a systematic review, 30 two as narrative reviews, 31,32 one as a systematic scoping review, 33 one as a thematic analysis review, and one as an integrative review 34 . The six review articles included 81 unique studies describing 47 unique interventions and 26 unique observational studies, 4 reviews, and 4 studies with mixed methodology.…”
Section: Principal Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…No date criteria were used in our search strategy, but all six reviews were published after 2015. Methods varied as follows: one review identified itself as a systematic review, 30 two as narrative reviews, 31,32 one as a systematic scoping review, 33 one as a thematic analysis review, and one as an integrative review 34 . The six review articles included 81 unique studies describing 47 unique interventions and 26 unique observational studies, 4 reviews, and 4 studies with mixed methodology.…”
Section: Principal Findingsmentioning
confidence: 99%
“… 33 Another review focused on interventions involving individuals with MCCs in decision making, 30 and four reviews focused on self‐management among those with MCC. Of the four reviews of self‐management, two described characteristics and challenges of self‐management, 31,35 one described the assessment of self‐management, 35 and one focused on self‐management interventions 34 . The two reviews of qualitative literature of challenges in self‐management of MCC identified the tendency of individuals with MCC to prioritize a dominant illness among multiple diagnoses, with a variety of processes underpinning this prioritization (and re‐prioritization) such as the chronological order of diagnoses, perceived contribution of one disease to quality of life or survival, or condition with an unpredictable course 31,35 .…”
Section: Principal Findingsmentioning
confidence: 99%
See 3 more Smart Citations